2018
DOI: 10.1002/jaba.468
|View full text |Cite
|
Sign up to set email alerts
|

Shaping complex functional communication responses

Abstract: Response efficiency plays an important role in the initial success of functional communication training (FCT). Although low-effort functional communication responses (FCRs) have been shown to be most effective in replacing problem behavior; more developmentally advanced FCRs are favored later in the treatment process. Attempts to teach these more complex FCRs, however, often lead to the resurgence of problem behavior. In this study, we provide a detailed description of an effective shaping process applied with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 32 publications
(52 reference statements)
2
35
0
3
Order By: Relevance
“…Like Ghaemmaghami et al (), we taught specific FCRs for various activities as opposed to a an omnibus “My way” request (Hanley et al, ; Ghaemmaghami et al, ; Jessel et al, ). Unlike Ghaemmaghami et al (), we did not see persistence of problem behavior while we taught precise mands which may be because we taught mands for different toys whereas Ghaemmaghami et al () taught precise mands for different functional classes of reinforcement (i.e., escape, tangibles, and attention).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Ghaemmaghami et al (), we taught specific FCRs for various activities as opposed to a an omnibus “My way” request (Hanley et al, ; Ghaemmaghami et al, ; Jessel et al, ). Unlike Ghaemmaghami et al (), we did not see persistence of problem behavior while we taught precise mands which may be because we taught mands for different toys whereas Ghaemmaghami et al () taught precise mands for different functional classes of reinforcement (i.e., escape, tangibles, and attention).…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of the assessment and treatment model employed by Hanley et al () are promising and there have been numerous replications of the assessment process and initial stages of treatment (e.g., Ghaemmaghami, Hanley, & Jessel, ; Ghaemmaghami, Hanley, Jessel, & Landa, ; Ghaemmaghami, Hanley, Jin, & Vanselow, ; Jessel et al, ; Slaton, Hanley, & Raftery, ), there are fewer replications of the entire assessment and treatment process with evaluations of the social validity of the outcomes (Herman et al, ; Jessel et al, ; Santiago et al, ; Strand & Eldevik, ; Taylor et al, ), and there are limited data on the maintenance of effects. In addition, only three replications were published by authors who did not train with Dr. Hanley at the Life Skills Clinic at Western New England University (Herman et al, ; Strand & Eldevik, ; Taylor et al, ).…”
mentioning
confidence: 99%
“…The left panel shows that larger increases in effort of the alternative behavior are predicted to produce more resurgence of target behavior, and the right panels show that larger increases in effort of the alternative behavior are also expected to produce larger decreases in the rates of alternative behavior. There is existing evidence consistent with this prediction of RaC that increases in alternative-response effort can produce resurgence of problem behavior (see Ghaemmaghami et al, 2018). In addition, Ghaemmaghami et al (2018) showed that such resurgence might be reduced by employing a gradual shaping process in which progressively complex and effortful alternative responses are reinforced at a high rate.…”
Section: Asymmetrical Choice Situationsmentioning
confidence: 77%
“…There is existing evidence consistent with this prediction of RaC that increases in alternative-response effort can produce resurgence of problem behavior (see Ghaemmaghami et al, 2018). In addition, Ghaemmaghami et al (2018) showed that such resurgence might be reduced by employing a gradual shaping process in which progressively complex and effortful alternative responses are reinforced at a high rate. Although it is difficult to precisely quantify such a procedure with RaC at this point, the outcome of the procedure is at least conceptually consistent with RaC in terms of establishing and increasing the value of approximations to the terminal response relative to problem behavior.…”
Section: Asymmetrical Choice Situationsmentioning
confidence: 77%
“…The inconsistent inclusion of a skill‐building component in treatments for automatically maintained behavior contrasts with that of problem behavior maintained by social reinforcement, for which functional alternatives are frequently increased through a training program such as functional communication training (e.g., Greer, Fisher, Saini, Owen, & Jones, ), shaping (e.g., Ghaemmaghami, Hanley, Jessel, & Landa, ), chaining (e.g., Hanley, Jin, Vanselow, & Hanratty, ), and prompt fading (e.g., Torres‐Viso, Strohmeier, & Zarcone, ). One reason for this discrepancy may be the challenge in finding reinforcers for play skills that compete with the automatic reinforcer for problem behavior.…”
Section: Resultsmentioning
confidence: 99%